P3.199 Factors Affecting HIV Prevalence Among Clients of Female Sex Workers in 16 Districts of Southern India. (13th July 2013) - Thomas, T; Thamattoor, U; Banandur, P; Potty, R Subramanian; Mainkar, M K; Adhikary, R; Duchesne, T; Banadakoppa, R M; Alary, M
Abstract : Background: Clients of female sex workers (FSWs) are considered an important bridging population for HIV. This study aims to assess the impact of Avahan (India AIDS Initiative of Bill & Melinda Gates Foundation), through comparison of HIV prevalence between two surveys (2006–07 and 2009–10) among clients of FSWs across 16 districts in south India (n∼7, 000 per-round). Methods: Multilevel logistic regression analysis was performed using HIV as outcome, with individual variables at level 1 and district-level programme variables (from the Avahan computerised monitoring system) at level 2. Mean value of the programme indicators for the years 2007 & 2008 were used as district level variables. Results: HIV prevalence declined significantly from round 1 to round 2 (5.5% to 3.4%; p = 0.001). Clients' characteristics such as increased age (25–34 yrs-AOR = 2.22, 95% CI: 1.74.2.85, ≥ 35 yrs-AOR = 2.32, 95% CI: 1.75.3.07), being literate (AOR = 0.69, 95% CI: 0.58, 0.82), being separated/divorced/widowed compared to never married (AOR = 1.52, 95% CI: 1.02.2.26), had sex with 3 FSWs within past 6 months (AOR = 0.61, 95% CI: 0.43.0.87), anal sex with man/hijra in last 6 months (AOR = 1.48, 95% CI: 1.14, 1.91), being circumcised (AOR = 0.73, 95% CI: 0.57, 0.92) and had at least one STI symptom (AOR = 1.21, 95% CI: 1.00.1.46) were associated with being HIV positive. Among the programme variables, greater programme coverage was significantly associated with lower prevalence (AOR = 0.992, 95% CI: 0.985, 0.999). Conclusions: These results demonstrate that there was a decline in HIV prevalence among clients of FSWs over the course of the intervention and the districts with increased Avahan programme coverage had lower HIV prevalence. Further explorative analysis is required to understand the role of programme coverage on the reduction in HIV prevalence among clients in light of similar surveys among FSWs that showed a clearer association of increase in programme coverage between survey rounds and decrease in HIV.